O consumo simbólico do esporte e o jornalismo feminista: entrecruzamentos discursivos na representação da mulher esportista na imprensa feita por e para mulheres - Rocha, Camilla Rodrigues Netto da Costa (2020)
Feminist journalism is constructed as a space that aims to give women a voice, articulating in their agendas issues related to this sociological minority and turned to this audience specifically. Considering this context, this research chooses as an empirical object two feminist media vehicles produced by and aimed at women, the websites / blogs “Think Olga” and “Dibradoras” and aims to investigate their discursive strategies in order to understand, from their representations around sportswomen, what forms of symbolic consumption of sport emerge from these representations. For that, it adopts as theoretical perspectives the studies of gender/sex/sexuality and corporalities, besides the sport, that allow the investigation about bodies’ fluidity and the performativity, with their possible transgressions and/or adaptations. This investigation also permeates the notions of biosocialities and recognition, articulating them with the studies of symbolic consumption of sport. It adopts, as a methodological itinerary, the French Line Discourse Analysis (ADF) with emphasis on the issue of discursive formations. In other words, we will analyze what, in the materiality of a particular discourse (in this case, the representation of sportswomen), are the influences and coercions coming from other discourses also in circulation. It is expected, with this investigation, to approach how sportswomen are articulated by a media that intends to be feminist and to analyze which forms of symbolic consumption of sport are possible from these rearticulations in this production instance. As a result, the research points out the impact that the media representation, for being linked to the notion of “women”, causes in senses’ circulation. We also highlight the preponderance of the feminist media, which, when introducing sport to its consumers, circulates important and distinct meanings about sportswomen, resulting from deeper discursive clashes than the notion of sport suggests.